Bridging the Gap: Enabling Network IDS Research through Laboratory Development - Zy, Ahmad Turmudi; Suryadi, Dikky; Simarangkir, Manase Sahat H; Sidabutar, Jeckson; Ghofir, Abdul (Proceeding International Pelita Bangsa, 2023)
This research explores the critical connection between innovation in IDS technology and the establishment of advanced research laboratories. Through a diverse range of presentations, workshops, and discussions, participants will discover how these labs can bridge the gap between theoretical research and practical application, ultimately bolstering the defense of our interconnected world against cyber adversaries. Attendees will gain insights into the vital role that research laboratories play in advancing IDS technology, enhancing cybersecurity practices, and adapting to emerging threats. It addresses the pressing need for state-of-the-art laboratories that serve as fertile grounds for exploring novel IDS strategies, testing new detection algorithms, and simulating real-world cyberattacks.